Human Characteristics in Chatbots Cause an Impact on Customer Experience in The Banking Sector - Gonzalo Alva; Martin Caceres (Journal of Technology Management & Innovation, 2025)
This study investigates how the human characteristics of chatbots, such as warmth and competence, impact customer experience in the banking sector of Lima, Peru. Given the increasing adoption of artificial intelligence in the financial sector, this analysis is warranted by the need to understand its influence on user satisfaction and loyalty. Through a non-experimental quantitative methodology and virtual surveys, we evaluated whether the personalization and social presence of chatbots enhance user perception, particularly among younger generations. The findings reveal that, while users value these characteristics, neutral responses persist, indicating a lack of emotional connection in certain cases. This underscores the importance of optimizing chatbot implementation to maintain competitiveness in the digital age. This study highlights the relevance of tailoring AI solutions to customer expectations to foster a more positive and personalized experience. During the course of this study, we found no similar research conducted within the Peruvian market designed to measure the impact of relevant variables on consumer experience in the banking sector when interacting with a chatbot.